Development and validation of spiritual care module for breast cancer women undergoing chemotherapy - Shili, Cheng (2025)
Nurses play a crucial role as caregivers for cancer patients, and providing spiritual care (SC) has become an integral part of their responsibilities. Despite this, the spiritual needs (SN) of cancer patients are often overlooked in clinical practice. Breast cancer (BC) women, regardless of the disease stage, have diverse and significant SN. This study aims to develop and validate a SC module for BC women undergoing chemotherapy. This study consisted of Phase 1, 2, and 3. Phase 1 was a cross-sectional design done in the Guangxi Medical University Cancer Hospital in China from December 2022 to April 2023. SN was assessed using the Spiritual Needs Scale (SNS). 173 BC chemotherapy women were recruited using purposive sampling included in this phase. SPSS 27.0 was used for statistical analyses, and the data were analysed using descriptive statistics. Phase 2 was designing and developing an e-module, the "Healing Light" based on the key SN of Phase 1 and the literature review. Phase 3 was the content validation using a Fuzzy Delphi method with eight experts from medical, nursing, educational, and SC. The results of Phase 1 showed a high level of SN among BC women undergoing chemotherapy (84.20 ± 12.86). Three main SN identified were "hope and peace", "meaning and purpose", and "acceptance of dying". For Phase 2, the developed SC e-module Healing Light consists of an introduction to BC and spirituality, cultivating hope and achieving inner peace, finding meaning and purpose in life, accepting the present and looking forward, and supportive information. Phase 3 results of the content validation showed that the content of Healing Light had gained expert consensus with a value above 75%, the threshold value (d) ≤ 0.2, and the fuzzy score (A) ≥ α – cut-off value = 0.5. In conclusion, this study developed and validated an SC e-module, Healing Light tailored to the Chinese cultural context. Healing Light will serve as a crucial reference and foundation for creating effective psychological interventions for BC women receiving chemotherapy. Additionally, it provides nurses with a valuable tool to deliver SC and empowers BC women to manage their spirituality, thus enhancing their spiritual health and quality of life (QoL).